Peran Jaksa Penuntut Umum dalam Menegakkan Keadilan bagi Korban Tindak Pidana Penempatan Pekerja Migran Indonesia melalui Upaya Hukum atas Putusan Hakim (Studi pada Kejaksaan Negeri Lampung Tengah) - Muhammad Arsy Perwira Witono (PT. Hasba Edukasi Mandiri, 2025)
The illegal placement of Indonesian Migrant Workers (PMI) remains a serious issue in Indonesia, with many victims trapped in exploitation and abuse by labor syndicates. The Public Prosecutor (JPU) plays a key role in enforcing the law against the perpetrators of this crime, but the implementation of justice is often hindered by discrepancies between the prosecutor's demands and the court's verdicts. This study aims to analyze the role of the Public Prosecutor in upholding justice for victims of illegal PMI placement through legal efforts such as appeals and cassation, as well as identifying the obstacles encountered in the legal process. The research uses a qualitative approach with in-depth interviews with the Public Prosecutor, judges, and migrant worker protection agencies. The findings indicate that although the Public Prosecutor strives to demand appropriate penalties, various external and internal factors influence judicial decisions, thus justice for victims has not been fully realized. This study provides recommendations to improve coordination among law enforcement agencies and enhance protection for Indonesian migrant workers.